Komunikasi Antarpribadi Guru dan Siswa Dalam Mengurangi Dampak “Learning Loss” Pada Pembelajaran Daring di Masa Pandemik (Studi Kasus di SDIT Cordova 1 Tangerang - Ayoedia Gita Citrayomie; Rizki Ayu Budi Pratiwi; Rachma Tri Widuri (Lembaga Layanan Pendidikan Tinggi Wilayah III DKI Jakarta, 2023)
The pandemic that lasted in Indonesia for approximately two years caused various changes in conditions, including in education. The learning system that usually takes place face-to-face has shifted to online meetings. This also reduces the duration of the learning process. Changes that occur require adaptation from various parties, including parents, teachers, and students. Various obstacles in the online learning process cause learning loss for some students. This situation certainly requires special attention, especially the role of teachers as guardians of students in schools. This study aims to determine the process of interpersonal communication between teachers and students to reduce the impact of learning loss experienced by students. By using qualitative research methods through in-depth interviews with several informants, namely several teachers, conducted at SDIT Cordova 1 Tangerang in grades 1, 2, and 3, it was found that interpersonal communication made by teachers to students was persuasive. This is done to provide understanding by directing students to have high learning motivation and overcome the impact of learning loss on students. Delivering convincing messages in interpersonal communication facilitates communication between teachers and students. In implementing interpersonal communication at SDIT Cordova 1, the teachers always try to direct students through communication in a good way and help to overcome the challenges students face in the subject and beyond. Therefore, the learning loss problem can be overcome